Tumour Angiogenesis in Rectal Cancer-Computer-Assisted Endosonographic and Immunohistochemical Methods for Assessment - Ludmila, Tankova; Kovatchki, Daniel; Stoilov, Georgi; Gegova, Antonina; Terziev, Ivan (IntechOpen, 2011)
None